The Integrated Deep Learning Literacy, Orientation, Collaboration, and Reflection (LOK-R) Learning Model on Elementary School Students' Social Studies Learning Outcomes - Sovia Lorenza; Badeni; Endang Widi Winarni; Osa Juarsa; Abdul Muktadir (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
The low learning outcomes of students in social studies are the fundamental reason for the use of the Deep Learning integrated LOK-R model in elementary schools. This study aims to analyze the effect of the Deep Learning integrated LOK-R model on social studies learning outcomes. This type of research uses a quantitative method with a quasi-experimental design. The study population consisted of 300 elementary school students. The sample in this study was class VA as a control class with 25 students and VC as an experimental class with 21 students. The sample was selected using simple random sampling. Data collection techniques were observation, testing, and documentation. The collected data were analyzed using descriptive statistics and inferential statistics. The results of this study indicate that the Deep Learning-integrated LOK-R model affects social studies learning outcomes. The results of the hypothesis test indicate a significant difference in the average social studies learning outcomes between the control and experimental classes. Based on the study, the Deep Learning-integrated LOK-R model has a significant effect on the social studies learning outcomes of fifth-grade elementary school students. The study's implications indicate that a student-centered, deep-understanding-based approach can significantly improve the quality of the process and learning outcomes. The implementation of the LOK-R model, integrated with Deep Learning, encourages students not only to memorize facts but also to understand social concepts critically, analytically, and contextually.